Influence of Blockchain Technology Application in Education on Online Teaching Resources Sharing - Hao, Zhongchao; bin Yahya, Mohd Yamani; Lu, Jianwei (International Journal of Emerging Technologies in Learning (iJET), 2023)
With the continuous expansion of educational view, blockchain technology develops into the cutting-edge applied science and technology of educational information construction. Blockchain technology can effectively solve such problems as information security and trust crisis in the current application of big data in online education by virtue of its characteristics of decentralization, traceability, multi-party consensus mechanism, and high trust. Blockchain technology is conducive to protecting online educational resources, strengthening the transparency of online teaching resources, simplifying the copyright transaction process, and thus enhancing the scientific and technological innovation ability of teachers. Studies regarding the blockchain technology application in education were analyzed, and the influences of the four aspects of the blockchain technology application in education on online teaching resource sharing were explored. Results showed that the Cronbach α coefficient of the questionnaire designed in this research was 0.856, and the KMO value was 0.859, indicating its good reliability and validity. The cross-institutional learning record storage space, learning certificate management mechanism, and collaboratively developed educational ecosystem of the blockchain technology application in education obviously promoted online teaching resource sharing at a significance level of 5%. The results are important reference values for strengthening the integration of educational resources under blockchain technology, improving the application mechanism of online digital educational resources, and improving the accurate service quality of online educational resources.